2019
DOI: 10.1016/j.ebiom.2018.11.041
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal brown adipose tissue mitochondrial structure and function in IL10 deficiency

Abstract: BackgroundInflammation is the most relevant mechanism linking obesity with insulin-resistance and metabolic disease. It impacts the structure and function of tissues and organs involved in metabolism, such as the liver, pancreatic islets and the hypothalamus. Brown adipose tissue has emerged as an important component of whole body energy homeostasis, controlling caloric expenditure through the regulation of non-shivering thermogenesis. However, little is known about the impact of systemic inflammation on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 71 publications
2
23
0
Order By: Relevance
“…By extending across the entire organelle and minimizing the curved regions of the cristae, brown fat mitochondria thus have less available space to place ATP synthase dimers, while still maintaining a large region for placement of ETC complexes. In contrast, in heart and skeletal muscle mitochondria where energetic efficiency is critical to sustaining muscle contraction, the lamellar cristae display much more curvature than in brown adipose tissue despite similar cristae densities (Kang et al, 2009;Picard et al, 2015;de-Lima-Junior et al, 2019). In each case, cristae structure appears to be tuned to support the energetic needs of the respective cells.…”
Section: Cristae Shapementioning
confidence: 99%
“…By extending across the entire organelle and minimizing the curved regions of the cristae, brown fat mitochondria thus have less available space to place ATP synthase dimers, while still maintaining a large region for placement of ETC complexes. In contrast, in heart and skeletal muscle mitochondria where energetic efficiency is critical to sustaining muscle contraction, the lamellar cristae display much more curvature than in brown adipose tissue despite similar cristae densities (Kang et al, 2009;Picard et al, 2015;de-Lima-Junior et al, 2019). In each case, cristae structure appears to be tuned to support the energetic needs of the respective cells.…”
Section: Cristae Shapementioning
confidence: 99%
“…Using a mouse model of chronic systemic inflammation, which exhibits increased circulating levels of inflammatory cytokines and abnormal regulation of both innate and adaptive immune responses, mitochondrial swelling is detected with severe damage of the cristae, in addition to reduced cold-induced thermogenic capacity and UCP1-dependent mitochondrial respiration (197). Furthermore, low grade inflammation in BAT in obesity is found as a contributor to excess reactive oxygen species (ROS) production and associated oxidative stress, which may cause mitochondrial dysfunction (198)(199)(200)(201)(202).…”
Section: Mitochondrial Function Is Affected By Inflammatory Pathwaysmentioning
confidence: 99%
“…IL-10 can regulate lipid metabolism by affecting mitochondrial respiratory function. As an immunomodulatory factor, the function of regulating metabolic balance is easy to be ignored 41 . Through electron microscopy and oil red staining, we found that IL-10 secreted by MSCs can affect liver steatosis induced by hepatectomy.…”
Section: Discussionmentioning
confidence: 99%